2023
DOI: 10.2174/1570159x20666220817140737
|View full text |Cite
|
Sign up to set email alerts
|

Energy Crisis Links to Autophagy and Ferroptosis in Alzheimer’s Disease: Current Evidence and Future Avenues

Abstract: Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases worldwide. The occult nature of the onset and the uncertainty of the etiology largely impede the development of therapeutic strategies for AD. Previous studies revealed that the disorder of energy metabolism in the brains of AD patients appears far earlier than the typical pathological features of AD, suggesting a tight association between energy crisis and the onset of AD. Energy crisis in the brain is known to be induced by the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 255 publications
0
1
0
Order By: Relevance
“…It has been found that down-regulation of miR-22 can significantly alleviate the apoptosis of PC-12 cells induced by LPS and achieve the purpose of treating diseases ( Wang Y. et al, 2022 ). Of course, there are many types of nerve cell death, including apoptosis, pyroptosis, necrosis, and ferroptosis ( He et al, 2022 ; Jin et al, 2022 ; Mangalmurti and Lukens, 2022 ). Whether ncRNAs can achieve the purpose of treating diseases by regulating different types of death is also worthy of further study in the future ( Li W. et al, 2022 ; Wang J. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that down-regulation of miR-22 can significantly alleviate the apoptosis of PC-12 cells induced by LPS and achieve the purpose of treating diseases ( Wang Y. et al, 2022 ). Of course, there are many types of nerve cell death, including apoptosis, pyroptosis, necrosis, and ferroptosis ( He et al, 2022 ; Jin et al, 2022 ; Mangalmurti and Lukens, 2022 ). Whether ncRNAs can achieve the purpose of treating diseases by regulating different types of death is also worthy of further study in the future ( Li W. et al, 2022 ; Wang J. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%